Flavonoid Phloretin Inhibits Adipogenesis and Increases OPG Expression in Adipocytes Derived from Human Bone-Marrow Mesenchymal Stromal-Cells - Antonio Casado-Díaz (MDPI AG, 2021)
Phloretin (a flavonoid abundant in apple), has antioxidant, anti-inflammatory, and glucose-transporter inhibitory properties. Thus, it has interesting pharmacological and nutraceutical potential. Bone-marrow mesenchymal stem cells (MSC) have high differentiation capacity, being essential for maintaining homeostasis and regenerative capacity in the organism. Yet, they preferentially differentiate into adipocytes instead of osteoblasts with aging. This has a negative impact on bone turnover, remodeling, and formation. We have evaluated the effects of phloretin on human adipogenesis, analyzing MSC induced to differentiate into adipocytes. Expression of adipogenic genes, as well as genes encoding OPG and RANKL (involved in osteoclastogenesis), protein synthesis, lipid-droplets formation, and apoptosis, were studied. Results showed that 10 and 20 µM phloretin inhibited adipogenesis. This effect was mediated by increasing beta-catenin, as well as increasing apoptosis in adipocytes, at late stages of differentiation. In addition, this chemical increased OPG gene expression and OPG/RANKL ratio in adipocytes. These results suggest that this flavonoid (including phloretin-rich foods) has interesting potential for clinical and regenerative-medicine applications. Thus, such chemicals could be used to counteract obesity and prevent bone-marrow adiposity. That is particularly useful to protect bone mass and treat diseases like osteoporosis, which is an epidemic worldwide.